Zakat Utilization Model Canvas: Alleviating Poverty through Stockbreeding Program - Sari, Aisha Putrina; Anggraini, Dita; Zaenardi, Adhitya Kusuma (Center of Strategic Studies (PUSKAS) BAZNAS, 2023)
One of the poverty alleviation programs mostly carried out by zakat institutions is the mustahiq utilization program through stockbreeding empowerment. Geographical conditions, demographics, and the enormous potential for qurban’s meat are a few factors that support zakat-based stockbreeding programs. This study aims to determine whether the stockbreeding programs run by the zakat institution positively impact mustahik. The impact measurement was carried out using mixed methods, namely the BAZNAS Welfare Index (BWI) and the poverty indicator approach to determine the number of mustahik farmers lifted out of poverty. The results show that in 2021 the BWI value of the BAZNAS stockbreeding program is classified under the Good category (0.78) and managed to transform 81% of mustahiq into muzaki. Furthermore, this study will be the first to explain the business process of stockbreeding programs by using a modification of the Business Model Canvas, the Zakat Utilization Model Canvas (ZUMC). We recommend ZUMC to be implemented by zakat institutions to help them design stockbreeding programs to improve the quality of life of mustahiq.